2002
DOI: 10.1063/1.1466830
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of solid nitromethane: Effects of high pressure and molecular vacancies

Abstract: The combined effect of pressure and molecular vacancies on the atomic structure and electronic properties of solid nitromethane, a prototypical energetic material, is studied at zero temperature. The self-consistent charge density-functional tight-binding method is applied in order to investigate changes induced in the band gap of this system by uniform and uniaxial strain of up to 70%, corresponding to static pressure in the range of up to 200 GPa. The effects of molecular vacancies with densities ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 69 publications
5
67
1
Order By: Relevance
“…Other theoretical studies on nitromethane [55][56][57][58], hexanitrostilbene (HNS) [34], pentaerythritol tetranitrate (PETN) [59], FOX-7 (2,2-dinitroethylene-1,1-diamine) [60], TATB [61,62], b-HMX [63,64], TNAD (trans-1,4,5, 8-tetranitrodecahydro-pyrazino-[2,3-b]pyrazine) [65], and bicyclo-HMX (cis-1,3,4,6-Tetranitrooctahydroimidazo- [4,5-d] imidazole) [66] have shown that these materials also indicate some band gap lowering under compression. According to the band gap criterion, it can be concluded that these energetic materials become more and more sensitive with the pressure increasing.…”
Section: Effect Of Hydrostatic Compressionmentioning
confidence: 99%
“…Other theoretical studies on nitromethane [55][56][57][58], hexanitrostilbene (HNS) [34], pentaerythritol tetranitrate (PETN) [59], FOX-7 (2,2-dinitroethylene-1,1-diamine) [60], TATB [61,62], b-HMX [63,64], TNAD (trans-1,4,5, 8-tetranitrodecahydro-pyrazino-[2,3-b]pyrazine) [65], and bicyclo-HMX (cis-1,3,4,6-Tetranitrooctahydroimidazo- [4,5-d] imidazole) [66] have shown that these materials also indicate some band gap lowering under compression. According to the band gap criterion, it can be concluded that these energetic materials become more and more sensitive with the pressure increasing.…”
Section: Effect Of Hydrostatic Compressionmentioning
confidence: 99%
“…We obtain a volume strain of the order of 45%, a value for which abrupt changes of the atomic configuration are expected. 8,10 In fact, since the sample volume of our DAC was entirely filled with nitromethane, we are probably dealing with a nonhydrostatic compression. It has been shown that for pressures above 2 GPa, the crystal a axis is the most compressible.…”
Section: Vibrational Energy Transfer Between the Internal And Externamentioning
confidence: 99%
“…9,12,13 Along the a-axis, the methyl group of one molecule faces the nitro group on the second. According to Margetis et al, 8 the a compression involves rotation of the methyl groups and reorientations of the molecules, primarily via relative translations and rotations around their C-N axes. Yarger and Olinger 13 suggested that this process may lead to the formation of chains of molecules, linked by bonds between the nitro and methyl groups of the neighbouring molecules.…”
Section: Vibrational Energy Transfer Between the Internal And Externamentioning
confidence: 99%
“…In contrast, the production of H 2 O would takes nine steps in a previous proposed model. [9] It general, the oxidation of H atoms to form H 2 O molecules releases a large amount of energy. In contrast, we do not expect formation of C=O molecules to contribute much to the energy release, since C=O forms largely from breaking off from the (CH 2 NO 3 ) 3 -CH-C=O moiety, an exothermic process.…”
Section: Resultsmentioning
confidence: 99%
“…[6] This charge dependent energy contribution improves chemical transferability significantly, resulting in improved values of reaction energies for many organic molecules and biomolecules containing H, C, O and N. [7] In this work, we used the DFTB parameters employed in the previous studies of thermal decomposition of the explosive HMX and nitromethane . [8][9] We studied the decomposition of PETN in a constant NVT ensemble (T= 4200 K and € ρ =2.39 g/cc). The initial state of simulation was constructed by scaling the experimental PETN crystal lattice parameters hydrostatically with ambient molecular structure to achieve desired density.…”
Section: Computational Detailsmentioning
confidence: 99%